2008
DOI: 10.1038/ijo.2008.166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ileal fat perfusion on satiety and hormone release in healthy volunteers

Abstract: Objective: The ileal brake is a feedback mechanism activated by nutrients, especially fat, with marked effects on satiety. The effects of low doses of ileal fat on satiety are largely unknown. We therefore studied the effect of ileal vs oral delivery of low doses of fat on satiety and gut peptide secretion. Design: Randomized, single-blind crossover design. Subjects: Sixteen healthy, normal-weight volunteers (6 male; mean age 26 years, mean body mass index 22.4). Intervention: Participants were intubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 40 publications
2
60
1
Order By: Relevance
“…Circulating PYY 3-36 binds to Y2 receptors on the presynaptic terminals of hypothalamic neuropeptide Y (NPY) and agouti-related protein (AgRP) neurons, and inactivation of these neurons is associated with the induction of anorexia [186]. PYY is a major regulator of the ileal brake in that it acts to inhibit further food intake once nutrients, and especially lipids, have reached the distal small intestine (ileum) [187][188][189][190][191][192][193][194][195][196]. The density of PYY cells is generally decreased in sporadic IBS (Table 1.1 and Fig.…”
Section: Irritable Bowel Syndrome and Appetite-regulating Gut Hormonesmentioning
confidence: 99%
“…Circulating PYY 3-36 binds to Y2 receptors on the presynaptic terminals of hypothalamic neuropeptide Y (NPY) and agouti-related protein (AgRP) neurons, and inactivation of these neurons is associated with the induction of anorexia [186]. PYY is a major regulator of the ileal brake in that it acts to inhibit further food intake once nutrients, and especially lipids, have reached the distal small intestine (ileum) [187][188][189][190][191][192][193][194][195][196]. The density of PYY cells is generally decreased in sporadic IBS (Table 1.1 and Fig.…”
Section: Irritable Bowel Syndrome and Appetite-regulating Gut Hormonesmentioning
confidence: 99%
“…[42][43][44] Bile salts not only facilitate the adsorption of co-lipase and lipase, but also aid in the solubilization of the lipolysis products as they accumulate at the interface, into mixed micelles, allowing the transport to and through the gut mucosal surface [28]. The gut cell lining is then able to sense these nutrients and in response, secrete hormones and peptides that slow digestion and send signals to the brain that reduce appetite [45].…”
Section: Introductionmentioning
confidence: 99%
“…Landmark human studies have shown intestinal nutrient infusions can reduce food intake with rapid effects (48)(49)(50) , indicating that satiation signals must originate from the gut as well as post-absorptively. Numerous hormones, neurotransmitters and peptides stimulate orexigenic or anorexigenic responses.…”
Section: Impact Of the Exometabolome On Post-ingestive Appetite Regulmentioning
confidence: 99%